Peroneal tendon dislocation in talus fracture and diagnostic value of fleck sign - Ahmed Khalil Attia (10334814) (2020)
Introduction Talus fractures are not uncommon and one of the serious fractures in the foot and ankle. Peroneal tendon dislocation is one of the commonly missed soft tissue injuries which may have significant impact on the outcomes including persistent pain and swelling. They have been reported to be associated with calcaneum as well as talus fractures. Aim To report the incidence of peroneal tendon dislocation in talus fracture and the significance of fleck sign in the diagnosis of peroneal tendon dislocation. Methods We retrospectively reviewed 93 consecutive talus fractures in the period between 1/1/2011 to 1/11/2018. Inclusion criteria were: The patient underwent open reduction and internal fixation, had pre-operative CT scan that is available for review and three view ankle plain radiographs. Two independent authors review the radiographs for peroneal tendon dislocation, fleck sign and fracture classification, if any. Any dispute was resolved by the senior author. Patient records were reviewed for laterality, age, sex, mode of injury, associated injuries and operative interventions. 50 ankles met the inclusion criteria. 49 were males, mean age was 32.5 year and the predominant mode of injury was a fall from height. Results Peroneal tendon dislocation was found in ten patients out of 50 (20%). Risk of dislocation increased with severity of the fracture and neck fractures. Most of the dislocations were missed by surgeons and radiologist, and no additional procedures were done to address such an injury. The Fleck sign had a statistically significant correlation with peroneal tendons dislocations (p=.005) Conclusion Peroneal tendons dislocation is associated with as high as 20% of talus fractures. The authors recommend carefully reviewing CT scans by surgeons and radiologists alike to avoid missing such injury and allow for appropriate surgical approach utilization. The Fleck sign is a highly specific radiographic sign that has a statistically significant correlation with PT dislocation and hence we recommend intra-operative assessment of peroneal tendons in patients with the fleck sign. Other Information Published in: International Orthopaedics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00264-020-04534-9